2020
DOI: 10.3390/microorganisms8081146
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Honeybee (Apis mellifera) Gut Microbiota Throughout the Overwintering Period in Canada

Abstract: Microbial symbionts inhabiting the honeybee gut (i.e., gut microbiota) are essential for food digestion, immunity, and gut protection of their host. The taxonomic composition of the gut microbiota is dynamic throughout the honeybee life cycle and the foraging season. However, it remains unclear how drastic changes occurring in winter, such as food shortage and cold weather, impact gut microbiota dynamics. The objective of this study was to characterize the gut microbiota of the honeybee during the overwinterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 48 publications
9
25
0
1
Order By: Relevance
“…For example, the Phylum Cyanobacteria, which exists widely in water in the natural environment (Bartram et al 1999), was almost only found in the before overwintering sample. Notably, after overwintering, the dominant species composition of the samples in winter honeybees was the same, and there was no signi cant difference in their abundance; however, there was a large difference in beta diversity, which was consistent with the results of a previous study (Bleau et al 2020). Compared with other winter honeybees, honeybees defecated their waste and thus have a new intestinal environment after overwintering.…”
Section: Discussionsupporting
confidence: 88%
“…For example, the Phylum Cyanobacteria, which exists widely in water in the natural environment (Bartram et al 1999), was almost only found in the before overwintering sample. Notably, after overwintering, the dominant species composition of the samples in winter honeybees was the same, and there was no signi cant difference in their abundance; however, there was a large difference in beta diversity, which was consistent with the results of a previous study (Bleau et al 2020). Compared with other winter honeybees, honeybees defecated their waste and thus have a new intestinal environment after overwintering.…”
Section: Discussionsupporting
confidence: 88%
“…Their bodies are colonized by microbial communities orally by means of social interactions with nurse bees within a few days of emergence [ 51 , 52 ]. During metamorphosis into pupae, the gut bacteria are excreted via defecation along with the gut epithelium, and the next colonization starts due to trophallaxis, contact with other bees, as well as from the hive [ 53 ]. The abundance of bacteria in the whole gut reaches its peak 3–5 days post-adult emergence [ 54 ].…”
Section: Honeybee Microbiotamentioning
confidence: 99%
“…There are two Gram-positive species belonging to phylum Firmicutes that are ubiquitous and abundant; namely, Lactobacillus Firm-4 and Lactobacillus Firm-5, which inhabit the distal rectum [ 2 , 59 ]. In the majority of adult workers, Bifidobacterium asteroides is also found (albeit with much lower abundance) [ 53 , 61 ]. The mentioned bacterial species clusters are the most essential microorganisms in the honeybee gut, the so-called “core bacteria” [ 64 ].…”
Section: Honeybee Microbiotamentioning
confidence: 99%
See 2 more Smart Citations